Methods and models to investigate the physicochemical functionality of pulmonary surfactant. (October 2021) - Ravera, Francesca; Miller, Reinhard; Zuo, Yi Y.; Noskov, Boris A.; Bykov, Aleksei G.; Kovalchuk, Volodymyr I.; Loglio, Giuseppe; Javadi, Aliyar; Liggieri, Libero
Abstract: The pulmonary surfactant (PS) is a complex mixture of lipids and proteins dispersed in the aqueous lining layer of the alveolar surface. Such a layer plays a key role in maintaining the proper lung functionality. It acts as a barrier against inhaled particles and pathogens, including viruses, and may represent an important entry point for drugs delivered via aerosols. Understanding the physicochemical properties of PS is therefore of importance for the comprehension of pathophysiological mechanisms affecting the respiratory system. That can be of particular relevance for supporting the development of novel therapeutic interventions against COVID-19–induced acute respiratory distress syndrome. Owing to the complexity of the in vivo alveolar lining layer, several in vitro methodologies have been developed to investigate the functional and structural properties of PS films or interfacial films made by major constituents of the natural PS. As breathing is a highly dynamic interfacial process, most applied methodologies for studying PSs need to be capable of dynamic measurements, including the study of interfacial dilational rheology. We provide here a review of the most frequently and successfully applied methodologies that have proven to be excellent tools for understanding the biophysics of the PS and of its role in the respiratory mechanics. This overview also discusses recent findings on the dynamics of PS layers and the impact of inhalable particles or pathogens, such as the novel coronavirus, on its functionality.